2015
DOI: 10.1186/s13063-015-0909-5
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-based cognitive therapy for inflammatory bowel disease patients: findings from an exploratory pilot randomised controlled trial

Abstract: BackgroundInflammatory bowel disease (IBD) is a chronic gastrointestinal condition with a relapsing disease course. Managing the relapsing nature of the disease causes daily stress for IBD patients; thus, IBD patients report higher rates of depression and anxiety than the general population.Mindfulness-based Cognitive Therapy (MBCT) is an evidence-based psychological program designed to help manage depressive and stress symptoms. There has been no randomized controlled trial (RCT) testing the use of MBCT in IB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 78 publications
1
68
0
Order By: Relevance
“…The findings from this qualitative study are consistent with and supplement the quantitative data findings from the pilot RCT [33] which showed that depression and anxiety improved at post intervention and 6-month follow-up from baseline in the intervention arm. The findings of this study extend the findings of the pilot in few ways.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The findings from this qualitative study are consistent with and supplement the quantitative data findings from the pilot RCT [33] which showed that depression and anxiety improved at post intervention and 6-month follow-up from baseline in the intervention arm. The findings of this study extend the findings of the pilot in few ways.…”
Section: Discussionsupporting
confidence: 87%
“…All participants who completed the post intervention assessments from both arms were invited to participate in the focus groups as well as to complete a free text postal survey. Further details about the full design of the pilot RCT is published elsewhere [32, 33]. …”
Section: Methodsmentioning
confidence: 99%
“…Selective serotonin reuptake inhibitors and serotonin norepinephrine reuptake inhibitors such as duloxetine were effective pharmacologic treatments for psychological distress among IBD patients 58,59. Compared with standard-care treated patients, those who received additional cognitive behavioral therapy reported greater improvements in anxiety, depression and quality of life 6062. All the aforementioned therapies are aimed at anxiety and depression directly.…”
Section: Discussionmentioning
confidence: 99%
“…Interested participants then registered their interest with the researcher by telephone or email. This was followed up with a screening visit with the researcher and then informed written consent was obtained [46]. ”…”
Section: Methodsmentioning
confidence: 99%